PENGARUH GOOD CORPORATE GOVERNANCE, STRUKTUR MODAL DAN OPINI AUDIT TERHADAP NILAI PERUSAHAAN - Ratih Qadarti Anjilni; Zefanya (Jurnal Nusa Akuntansi, 2026)
This research was conducted to analyze the influence of Good Corporate Governance, Capital Structure and Audit Opinion on Company Value. The research was conducted on infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) in 2019 – 2023. The research methodology used is panel data regression, sample selection is carried out using the purposive sampling method so that 30 companies are obtained as research samples and the period studied is 5 years, from 2019 to 2023 so that there are 150 samples. The data used is taken from the audited financial statements and the annual reports published by each of the companies studied. Hypothesis testing was carried out using the Eviews series 12 application. The results of the study show that partially Institutional Ownership has an effect on Company Value, Audit Committee has no effect on Company Value, Capital Structure has an effect on Company Value and Audit Opinion has no effect on Company Value. Simultaneously, Good Corporate Governance, Capital Structure and Audit Opinion have a effect on the Company's Value.